2014
DOI: 10.1089/pho.2013.3688
|View full text |Cite
|
Sign up to set email alerts
|

Application of Optical Coherence Tomography to Identify Pulp Exposure During Access Cavity Preparation Using an Er:YAG Laser

Abstract: Objective: The study aimed to evaluate the ability of optical coherence tomography (OCT) to guide and identify pulp exposure using an erbium: yttrium-aluminum-garnet (Er:YAG) laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Micro-CT was used as a reference standard. Up to our knowledge, DM results have not yet been compared to micro-CT results before, while micro-CT has been used as a reference standard to evaluate OCT results in several studies [26,27]. The Spearman correlation between DM and OCT was low in addition to the low sensitivity and specificity of OCT. McNemar's test showed a significant difference between DM and OCT. One reason for the lower performance of OCT may be that the resolution of OCT was not high enough, resulting in somewhat blurred images without clear borderlines.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-CT was used as a reference standard. Up to our knowledge, DM results have not yet been compared to micro-CT results before, while micro-CT has been used as a reference standard to evaluate OCT results in several studies [26,27]. The Spearman correlation between DM and OCT was low in addition to the low sensitivity and specificity of OCT. McNemar's test showed a significant difference between DM and OCT. One reason for the lower performance of OCT may be that the resolution of OCT was not high enough, resulting in somewhat blurred images without clear borderlines.…”
Section: Discussionmentioning
confidence: 99%
“…Since OCT has the ability to detect tiny objects, the applications of the OCT in the field of dentistry have been studied [1,3,4,16]. Also, it could potentially be applied to provide detailed information about tooth cracks, such as micro-fractures, and may thus be a powerful noninvasive and reversible method of diagnosing cracked-tooth syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…SL was defined as the gold standard in this study, because section images were obtained non-destructively. Previous studies have reported the maximum dentin thickness penetrable by SS-OCT laser as <1.69 mm [5][6][7]9 . Other studies have reported the depth range of SS-OCT imaging in dental hard tissues as approximately 2.0 mm 10 .…”
Section: Discussionmentioning
confidence: 96%
“…As noted above, radiographic procedures possess some limitations. A few studies suggested that SS-OCT might detect the pulp dentin complex 5,6 . It has been reported that, using CT as a gold standard, spectral-domain OCT (SD-OCT), a type of OCT often employed in ophthalmology, successfully detected the pulp dentin complex 7 .…”
Section: Introductionmentioning
confidence: 99%